2016
DOI: 10.1111/pde.12781
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hemangiomas in Twins: A Prospective Cohort Study

Abstract: These findings suggest that the origin of IHs is multifactorial and that predisposing factors such as birthweight, sex, and GA may interact with one another such that a threshold is reached for clinical expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
16
0
4
Order By: Relevance
“…10,29 Studies comparing IH in monozygotic and dizygotic twins found no evidence of zygosity as a risk factor. 12,14 We detected 2 concordant monozygotic sets of twins and 1 discordant monozygotic twin but only 1 concordant dizygotic set of twins. The low number of twins in our study prevents drawing further conclusions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…10,29 Studies comparing IH in monozygotic and dizygotic twins found no evidence of zygosity as a risk factor. 12,14 We detected 2 concordant monozygotic sets of twins and 1 discordant monozygotic twin but only 1 concordant dizygotic set of twins. The low number of twins in our study prevents drawing further conclusions.…”
Section: Discussionmentioning
confidence: 82%
“…Familial clustering has been reported, even though genetic predisposition is controversial. 6,7,10,[12][13][14] Evidence exists that some IHs are inherited. Using information from the Utah Population Database, Grimmer et al 15 reported a twofold increase in the risk ratio for hemangioma among siblings of an affected proband.…”
mentioning
confidence: 99%
“…Monozygotic twins also did not present an increased incidence of hemangioma within their own group, which shows that hereditary factors are not dominant factors in development of hemangioma and that hemangioma is more common among twin pairs with lower birth weight. 24 The retrospective nature of our study is a major limitation to detect the real frequency of the probable factors causing hemangioma. Authors of the study are in the opinion that there is a need for more extensive prospective research work to be done in this field to conclude that these factors constitute an absolute risk for development of hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Yüzonsekiz ikiz eşi üzerinde yapılan bir çalışmada, monozigotik ve dizigotik ikizlerde hemanjiom insidansı arasında fark bulunmamıştır. Bu da kalıtsal faktörlerin hemanjiom gelişiminde etkili dominant faktörler olmadığını göstermektedir (29).…”
Section: Bulgularunclassified